IMPLEMENTASI PEMBELAJARAN BERBASIS ETNOMATEMATIKA MELALUI PERMAINAN “TUJU” DI KELAS IV SD N 001 SAWAH BARU KECAMATAN KAMPA KABUPATEN KAMPAR - Tohari, Khamim; Witri, Gustimal; Guslinda, Guslinda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The background of this research is the lack of student and the lack of active students in the learning process. This study aims to determine the effect and differences in mathematics learning outcomes between students taught throught the game “Tuju” and by using conventional methods. Based on the result of the study found that there is an influence of the game “Tuju” on the results of learning mathematics in the experimental class with a large influence of 22.9%. in the control class and experimental class posttest, it was obtained tcount = 2,485 ≥ ttable = 2,072, so that there were differences in students’ mathematics learning outcomes between the control class and the experimental class.Key Words: Ethnomatematics, Game